Exposure assessment of pharmaceutical powders based on an environmental monitoring method: a pilot study - Fatma Demircan Yildirim; Ismail Ekmekci (Nofer Institute of Occupational Medicine, 2020)
Background About 8 million healthcare workers in the USA are potentially exposed to hazardous drugs or their toxic metabolites over a long period of time despite the fact that both the Occupational Safety and Health Administration and the European Parliament recommend the monitoring of exposure among workers dealing with substances which have carcinogenic, mutagenic or toxic effects on the reproductive system. The objective of this study is to determine exposure to active pharmaceutical ingredients (APIs) among pharmaceutical industry workers, and to develop a methodology which promotes the accurate monitoring, evaluation and control of exposure to active pharmaceutical ingredients, also in compliance with good manufacturing practice. Material and Methods The pilot study was designed in accordance with "Sterile Drug Products Produced by Aseptic Processing - Current Good Manufacturing Practice," issued by the U.S. Food and Drug Administration. The samples were collected with the swab technique which was recommended in the "Validation of Cleaning Processes (7/93)" guideline. The minimum numbers of locations (N L = 9) and sampling points (N L (T) = 63) were determined according to ISO 14644-1:2015 "Cleanrooms and Associated Controlled Environments" issued by the International Organization for Standardization. The samples were analyzed using an ultra performance liquid chromatography system, with an analytical method which was developed and validated according to "Q7A, Good Manufacturing Practice Guide for Active Pharmaceutical Ingredients" issued by the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use. The low limit of quantification of the employed method (17 ng/ml) enables the determination of exposure at low concentrations. Results While contamination was detected in 43 (68.3%) of the 63 samples collected, 20 (31.7%) could not be detected. The environmental monitoring results ranged 0-15 000 ng/cm2 and the potential risk of exposure to API was considered to be >2 g. Conclusions The results clearly prove and reveal the magnitude of the hazard, both objectively and scientifically, when compared to the research which suggests that 10 ng/cm2 should be considered the prohibitory risk level in quantitative terms. Med Pr. 2020;71(6):649-63